Clinical profile and factors affecting surgical outcome of colorectal carcinoma in rural India: a study of 60 cases - Tamgadge, Lalit Vishvanath; Ahmed, Mohd Hamid Shafique; Ugane, Subodh Prabhakar; Gurav, Prakash Dattatray (International Surgery Journal, 2016)
Background: Colorectal carcinoma is the most common of the gastrointestinal tract malignancy. Aim of our study is to look for the clinical profile and factors affecting the surgical outcome of colorectal malignancy in rural India. Methods: In this study, 60 patients, whose surgery and follow up was performed by same correspondent Surgeons between years Nov 2011 to Oct 2013, were prospectively analyzed. Results: Of the 60 cases analyzed, we encountered the highest number of cases in the sixth and seventh decade in both sexes with male to female ratio 1:1. Alternating bowel habits, bleeding per rectum, giddiness and anorexia, weight loss, pain in abdomen were the most common presenting complaints with mean duration of symptoms was 6 months before diagnosis. Rectum and recto-sigmoid was the commonest site for occurrence of large bowel cancer (56.66%). Duke’s system of staging with Turnbull et al modification shows majority of cases (50.00%) in category C. Well differentiated adenocarcinoma is the commonest histological pattern noted in more than half of cases. Post-operative recurrence was detected in 16.67% of cases with 33.33% of cases have not had a detectable recurrence to date. Conclusions: Rectum being the commonest site for occurrence of colorectal malignancy, diet and other predisposing factors could not be implicated in the occurrence. Age, weight loss, emergency admission, operation type, advanced stage of disease at presentation, loss of regular follow-up and lower socio-economic status of patients of rural India significantly affect the outcome of surgery.